The biology of plants (New York : Insight Media, 1998)
This video contains : Part 1 - Photosynthesis, chloroplast structure, the light dependent reactions, the light independent reactions. Part 2 - Major plant groups, nonvascular plants, vascular plants
Editor and animator, Eric Robert Russell ; photograph and microvideograph, Bruce J. Russell
Keywords: Plants -- Reproduction; Plant diversity; Plant cells and tissues